Analysis Of Madrasah Principal Leadership In Improving Accreditation At MTS Al-Hasanah Medan - Neliwati Neliwati; Sri Rahayu Nasution Nasution; Sartika Hutasuhut; Sri Rezeqi Rafiqah Wardhah Manurung (EDUTEC : Journal of Education And Technology, 2022)
Accreditation is a special concern for a madrasa head because accreditation is a benchmark for good or bad quality in madrasas. This study intends to analyze how the leadership of a madrasa principal improves accreditation, this research was conducted at the Madrasah MTs Al-Hasana Medan. The method used in this study is a qualitative method with data collection techniques using interviews, documentation, and observation, while the validity of the data is carried out by reduction, display, and verification of research data. The results obtained are the stages in the accreditation process at MTs Al-Hasana Medan, namely preparation, implementation, and determination of accreditation. The principal's strategy in increasing accreditation is making work plans and programs, increasing professionalism, increasing student academic scores, developing student skills and potential, and conducting evaluations. Meanwhile, in leading the madrasah principal at MTs Al-Hasana Medan, he prioritizes deliberation, and democracy, involving all elements in the madrasa, prioritizing discipline and providing motivation.